THE INTELLIGENCE OF NATURE: HOW AI IS REDEFINING ORGANIC PRODUCTION IN 2026 - Kholmukhammedov Abdulaziz,; Avazbekova Jasmina, (TADQIQOTLAR, 2026)
Abstract: As the global organic market nears $136 billion, manufacturers face a "scaling gap" driven by high labor costs and strict chemical-free mandates. This article explores the shift toward Industry 5.0, where AI ensures predictive integrity through technologies  like  Hyperspectral  Imaging  and  E-Noses,  achieving  99%  detection accuracy for contaminants. We analyze the financial transition from variable labor to fixed  tech  investments,  which  typically  cuts  food  waste  by  30–40%.  Finally,  we examine  the  regulatory  landscape,  including  the  EU  AI  Act  and  ISO/IEC  42001, highlighting  how  AI-driven  precision  enables  large-scale,  sustainable  organic production while maintaining the "natural" promise. By synthesizing these technical and economic perspectives, the study provides a roadmap for producers navigating the digital transformation of heritage farming practices.